Local deformation and interfacial damage behavior of partially stabilized zirconia-reinforced metastable austenitic steel composites: Numerical simulation and validation - ChenChun Chiu; ShaoChen Tseng; Faisal Qayyum; Sergey Guk; ChingKong Chao; Ulrich Prahl (Materials & Design, 2023)
In this work, two simulation models were used to investigate the local deformation and damage behavior of partially stabilized zirconia-reinforced metastable austenitic steel composites and validated by experimental results. An in situ quasi-static tensile test on a miniature dog bone sample is performed under an electron microscope up to 6.4% true strain. A commercial digital image correlation program, VEDDAC, is used to process micrographs obtained at incremental strains to calculate the evolution of the local experimental strain distribution. The initial experimental micrograph was transformed into a geometry file for simulation model. In two different simulation models, the ceramic/matrix interface is assumed once to be perfect, and secondly, the interface is modeled using cohesive elements. The results showed that the stress concentration sites of the cohesive model continuously change along the interface because of the effect of debonding, while it maintains its position in the non-cohesive model. At 6.4 % global strain, the relative error of the strain between the DIC and the cohesive model is only 6 %. The numerical model with cohesive interface accurately predicts local stress and strain, as well as the position and evolution of damage accidents, and can therefore be reliably used by other researchers.